A interferência do sangue e soro fisiológico na solubilidade pH e componente iônico das obuturações retrógradas de MTA branco Ângelus® - Canali, Lys Cristina Furquim (2015)
The contamination by blood and tissue fluids of mineral trioxide aggregate (MTA) is usual in clinical environment in which moisture is always present. Aims to investigate the interference of white MTA when in contact with blood and saline, verifying changes on the solubility, pH level and ionic composition. A permanent maxillary central incisor was framed with vinyl polysiloxane and confectioned the mold, it reproduced 30 specimens of the tooth root in acrylic resin, apicoectomy performed 3 mm and retrograde obturation with MTA Angelus (Angelus, Londrina-Pr, Brazil) and divided into 03 groups placed in Eppendorf tubes. The first group was the control group (CG), with 10 specimens without liquids exposure. Groups 2 and 3 were experimental, 10 specimens each, have been added 1 ml saline group 2 (GE-S) and group 3 (GE-B), 1 ml of fresh human blood. Analyzed the solubility, with Micro CT scanning, the level of Hp, with measurer, and ionic composition by EDS, at 24 hours and after 168 hours. The GE-B showed the highest solubility, then CG and finally the GE-S, there was no statistically significant difference. Hidrogênico potential (Hp), it was observed that comparing the initial period with after 168 hours all groups showed a more alkaline Hp. Comparison among the groups is noticed a statistically significant difference between: GE-B x CG and GE-S x CG. In ionic composition the Calcium (Ca) founded with greater concentration, the GE-B favored greater release of hydroxyl ions. It concludes that the MTA Angelus in contact with blood and saline showed no interference in the solubility and small variations in the ionic composition.